Changes in antipsychotic drug usage and factors affecting the use of typical drugs based on nationwide health insurance data in South Korea. Issue 6 (30th June 2018) - Lee, Sang Uk; Ryu, Vin; Soh, Minah; Kim, Chul-Eung; Park, Subin; Roh, Sungwon; Oh, In-Hwan; Lee, Hye-Young; Choi, SungKu
Abstract : Objectives: To determine changes in antipsychotic drug usage in all South Korean patients with schizophrenia in 2011–2015 and factors affecting their utilisation in 2015. Design and setting: Retrospective cohort study using health insurance claims data on patients with schizophrenia in South Korea in 2011–2015. Participants: All treated patients with schizophrenia in South Korea in 2011–2015. The number of patients with schizophrenia was 171 302 in 2011, 175 488 in 2012, 177 763 in 2013, 180 079 in 2014 and 183 427 in 2015. Main outcome measures: Changes in antipsychotic drug usage and factors affecting the use of antipsychotics. Results: Among patients with schizophrenia, there were tendencies of decreased use of antipsychotic combination therapy of typical drugs (from 11.5% to 7.5%) but increased use of combination therapy of atypical drugs (from 21.8% to 29.0%). Factors affecting the use of typical drugs were sex, age, geographical region, type of benefits/insurances and type of medical institutions. Use of typical antipsychotics was increased by age (OR=1.02, 95% CI 1.02 to 1.02). It was higher in men (OR=1.27, 95% CI 1.23 to 1.30) than that in women. It was higher in Medicaid benefiters (OR=4.49, 95% CI 4.35 to 4.64) than that in patients with health insurance. Use of typical drugs was higher among patients treated in general hospitals (OR=1.46, 95% CI 1.32 to 1.64), primary hospitals (OR=3.25, 95% CI 2.95 to 3.59), long-term care hospitals (OR=3.00, 95% CI 2.59 to 3.49) and clinics (OR=8.87, 95% CI 8.06 to 9.76) compared with that in tertiary care hospitals. Compared with metropolitan region, higher use of typical antipsychotics was seen in Gangwon (OR=1.14, 95% CI 1.05 to 1.25), Jeolla (OR=1.32, 95% CI 1.26 to 1.39) and Gyeongsang (OR=1.14, 95% CI 1.10 to 1.18) provinces. Conclusions: Results of this study confirmed changes of antipsychotic drug usage from typical to atypical antipsychotics in the treatment of schizophrenia and identified factors affecting the use of typical drugs, in contrast with current treatment trend in South Korea. These results may be used in the improvement of a medical system.